The impact of the poem “Al-Munfarijah” by Abū al-Faḍl Ibn al-Naḥwī on the reader – a semantic reading - benhalis, houda (El Omda in Linguistics and Discourse Analysis, 2025)
The article revolves around an applied study of the poem ” elmonfaridja” , it received the attention of researchers, she gained international fame, by translating it into several languages, Which confirms its importance, summing up the effort of its creator in his experience as a man of thought and reform, and his awareness of the importance of the content of the text in nourishing minds and souls by spreading culture and science, by showing the extent of the impact of its diverse contents and style on the recipient by standing on the meaning through analysis and interpretation. So how did this poem affect the recipient? And what are its dimensions and characteristics?